THE ROLE OF THE PHARMACIST IN PAEDIATRIC PALLIATIVE CARE. Issue 9 (17th August 2016) - Khan, Jumana; Gaze, Sian; Tomlin, Stephen
Abstract : Aim: To explore what involvement pharmacists in the UK have in paediatric palliative care Objectives: 1. To determine the current roles and services provided by pharmacists to paediatric palliative care patients. 2. To establish how other members of the multidisciplinary team perceive the pharmacist's role and the extent to which they value the pharmacist's contributions. 3. To identify the references used by the multidisciplinary team to make clinical decisions about medication use in paediatric palliative care patients. Methods: An online questionnaire was designed and emailed to members of the Neonatal and Paediatric Pharmacist's Group and the Association of Paediatric Palliative Medicine. The questionnaire was also sent by post to selected community pharmacists as palliative care is often provided to children in a community setting. Results were analysed using Microsoft Excel and SPSS version 22. Results: A response rate of 27% (114/430) was achieved. Pharmacists reported supporting children receiving palliative care by supplying medicines, dealing with medication related enquiries and providing advice to nursing and medical staff on the compatibility and stability of drugs. The pharmacist's contributions were highly valued by other members of the paediatric palliative care team as a median rating of 9 (out of 10) was obtained. The results also showed that differences existed in the references used by pharmacists and other healthcare professionals–the Children's British National Formulary was the most commonly used reference across all disciplnes when caring for children requiring palliative care. Conclusion: This is one of the first studies to outline the roles of pharmacists working in paediatric palliative care and has highlighted that pharmacists have an important input in the care of these patients.